Argillipedoturbation and the development of rock fragment covers on Vertisols in the Ethiopian Highlands - Jan Nyssen; Jan Moeyersons; Jean Poesen; Mitiku Haile; Jozef A. Deckers (Belgeo)
The rock fragment cover of Vertisols and soils with vertic properties in the Northern Ethiopian Highlands is clearly in a stage of development. On a Vertisol near Enda Maryam Korar (Tigray), the rapid appearance at the surface of new rock fragments after field clearing has been monitored. This paper analyses the phenomenon of the upsqueezing of rock fragments in relation to the active polygonal structures of the Vertisols. Rock fragments, appearing yearly at the top of the Vertisol are shown to belong lithologically to deposits underlying the Vertisols. Given this stratigraphic situation and the activity of Vertisols in the study area, the rock fragment covers are thought to be squeezed up as a consequence of argillipedoturbation accompanying swell-shrink cycles in the Vertic horizon. The spatial distribution of upsqueezed rock fragments closely follows the polygonal pattern of crack bundles on top of the Vertisol. Based on yearly measurements of rock fragments appearing at the surface of a 78.5 m² cleared area, it is estimated that, on average, one rock fragment (0.11 kg) is squeezed up to the surface per m² per year. The mechanisms of this vertical transport come under discussion and have to explain why subvertical desiccation cracks are the loci of rock fragment appearance at the surface.